UPAYA PENGEMBANGAN KARAKTER RELIGIUS MELALUI KEGIATAN SHOLAWAT DI MADIN AL-IMAN PURWOREJO - Alwi, Muchammad; Imron, Ali; Agus Faisal, Vava Imam (DAS Institute, 2023)
In the era of globalization which is marked by the rapid development of technology and information, as well as the increasingly complex challenges of modernization, strengthening religious character has become an urgent need that cannot be ignored. Madrasah Diniyah (Madin) Al-Iman Purworejo, as one of the religious education institutions that has a high commitment to the formation of student character, faces quite a tough task in responding to this challenge. In an effort to answer these challenges, Madin Al-Iman strives to find effective methods and approaches to instill religious values ​​into students. One of the efforts made is through prayer activities, which are integrated comprehensively with the students. This research aims to examine in depth how prayer activities can play a role in developing the religious character of students at Madin Al-Iman Purworejo. The research method used is qualitative with a descriptive approach, where data is collected through observation, interviews and documentation. The research results show that prayer activities at Madin Al-Iman not only increase students' knowledge and love of the Prophet Muhammad SAW, but also strengthen religious values ​​such as sincerity, patience and obedience in daily life